2006
DOI: 10.1038/sj.ijo.0803193
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and all-cause mortality in a nationwide US cohort

Abstract: Objective: To investigate whether the nature of the relationship between body mass index (BMI (kg/m 2 )) and all-cause mortality is direct, J-or U-shaped, and whether this relationship changes as people age. Design: Prospective nationwide cohort study of US radiologic technologists (USRT). Subjects: Sixty-four thousand seven hundred and thirty-three female and 19 011 male certified radiation technologists. Methods: We prospectively followed participants from the USRT study who completed a mail survey in 1983-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
1
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 55 publications
2
112
1
10
Order By: Relevance
“…For example, we estimate that 45 participants would be required in each group to give a 90% probability at the 5% level of significance of detecting differences of 0.8±0.96 mmol l À1 in low-density lipoprotein cholesterol concentration. [43][44][45] Our findings are in keeping with prospective studies suggesting that 'optimal' BMI is around 23 in young, white runners 46 and young white men in the general population; 47 but, these findings cannot be generalized to women, older adults and other groups. Cross-sectional data cannot be used to infer causality, but several randomized, controlled trials have found that aerobic exercise is accompanied by preferential reductions in visceral adipose tissue.…”
Section: Discussionsupporting
confidence: 82%
“…For example, we estimate that 45 participants would be required in each group to give a 90% probability at the 5% level of significance of detecting differences of 0.8±0.96 mmol l À1 in low-density lipoprotein cholesterol concentration. [43][44][45] Our findings are in keeping with prospective studies suggesting that 'optimal' BMI is around 23 in young, white runners 46 and young white men in the general population; 47 but, these findings cannot be generalized to women, older adults and other groups. Cross-sectional data cannot be used to infer causality, but several randomized, controlled trials have found that aerobic exercise is accompanied by preferential reductions in visceral adipose tissue.…”
Section: Discussionsupporting
confidence: 82%
“…[1][2][3][4][5][6][7] Weight loss is known to be associated with improvement of intermediate risk factors for disease, 8 suggesting that weight loss would also reduce mortality. Although four retrospective, bariatric cohort studies have indicated that this may be the case, 9-12 the prospective, controlled, interventional studies showing that weight loss is in fact reducing mortality have been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown an inconsistent relationship between body mass index (BMI) and mortality risk, with associations being J-or U-shaped [4][5][6][7][8][9][10][11][12], direct linear [13][14][15][16] or absent [17,18]. This could be due to the inadequate control for smoking status and pre-existing chronic diseases, both of which are associated with a low BMI and an increased risk of death [19].…”
Section: Introductionmentioning
confidence: 99%